CRAFTING HISTORY: ANALYZING BANKIM CHANDRA CHATTOPADHYAY'S PIONEERING NOVELS - SUMANTA MONDAL (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
Bankim Chandra Chattopadhyay, a pivotal figure in Indian literature, played a crucial role in the evolution of the Indian novel during the 19th century. His pioneering works not only laid the foundation for modern Indian fiction but also infused it with a sense of national identity and cultural pride. This paper delves into the historical and cultural contexts of Chattopadhyay's novels, examining their impact on the Indian literary landscape and their enduring relevance. Chattopadhyay's novels, most notably